2012
DOI: 10.1186/1756-3305-5-69
|View full text |Cite
|
Sign up to set email alerts
|

A global map of dominant malaria vectors

Abstract: BackgroundGlobal maps, in particular those based on vector distributions, have long been used to help visualise the global extent of malaria. Few, however, have been created with the support of a comprehensive and extensive evidence-based approach.MethodsHere we describe the generation of a global map of the dominant vector species (DVS) of malaria that makes use of predicted distribution maps for individual species or species complexes.ResultsOur global map highlights the spatial variability in the complexity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
474
1
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 575 publications
(520 citation statements)
references
References 20 publications
4
474
1
10
Order By: Relevance
“…superpictus in Southeastern Iran. We do not suggest the use of DDT for indoor residual spraying in southeast Iran. recognized as the human malarial vector in the southern Palearctic region, central and southern Europe [6][7][8][9][10][11][12] , middle eastern countries, India, northern Africa, and Russia as well as new republic countries separated from the old Soviet Union [13,14] . Moreover, it is the main malarial vector widely found in Iran [14,[15][16][17][18] , and previous studies have indicated its both exophagic and endophilic behavior [19] .…”
Section: P E E R R E V I E W Abstract Abstract Anophelementioning
confidence: 99%
“…superpictus in Southeastern Iran. We do not suggest the use of DDT for indoor residual spraying in southeast Iran. recognized as the human malarial vector in the southern Palearctic region, central and southern Europe [6][7][8][9][10][11][12] , middle eastern countries, India, northern Africa, and Russia as well as new republic countries separated from the old Soviet Union [13,14] . Moreover, it is the main malarial vector widely found in Iran [14,[15][16][17][18] , and previous studies have indicated its both exophagic and endophilic behavior [19] .…”
Section: P E E R R E V I E W Abstract Abstract Anophelementioning
confidence: 99%
“…Below I explore some implications of this development. My debt especially to three recent reviews (Beebe et al, 2013;Sinka et al, 2012;White et al, 2011), which draw on much wider literatures than I shall do directly, will be very apparent.…”
Section: Anopheline Taxonomymentioning
confidence: 99%
“…In the 1980s, around 400 species of Anopheles were recognised (Bruce-Chwatt, 1985). Now, after much further work in genetics to supplement the morphology, 465 species are formally recognised and there are also over 50 unnamed members of species complexes (Sinka et al, 2012). Only a minority of all anopheline species have the capacity to transmit the five malaria parasites that normally infect people (Plasmodium falciparum, P. vivax, P. malariae, P. knowlesi and P. ovale), and fewer still do so frequently.…”
Section: Anopheline Taxonomymentioning
confidence: 99%
“…[6] Road transport from malarious areas is undoubtedly more important than air transport as a source of translocated mosquito vectors. Gauteng Province is the economic hub of SA.…”
Section: Epidemiological Aspects Of Odyssean Malariamentioning
confidence: 99%